(untitled) - Marr, Bernard (New Jersey, 2015)
This is a well-needed practical introduction to actually putting the topic into practice. Illustrated with numerous real-world examples from a cross section of companies and organisations, Big Data will take you through the five steps of the SMART model: Start with Strategy, Measure Metrics and Data, Apply Analytics, Report Results, Transform.
Keywords: Dữ liệu lớn,Quản lý,Information technology,Big data,Management,Công nghệ thông tin; Phương pháp thống kê,Management.,Statistical methods.,Quản lý